Ribavirin has an in vitro antiviral effect in rabies virus infected neuronal cells but fails to provide benefit in experimental rabies in mice - Appolinário, Camila Michele [UNESP]; Prehaud, Christophe; Allendorf, Susan Dora [UNESP]; Antunes, João Marcelo Azevedo Paula [UNESP]; Peres, Marina Gea [UNESP]; Lafon, Monique; Megid, Jane [UNESP] (My University, 2013)
Objectives: The nucleoside analog ribavirin is one of the antiviral drugs recommended in the management of several viral infections in humans. Although ribavirin has been used in rabies treatment, its efficacy has not been formally proven. The objectives were to study the effect of ribavirin on rabies virus (RABV) infection in neuronal cultures, to analyze whether orally-given ribavirin activates an innate immune response in the brain and whether ribavirin confers protection against brain infection in a model of experimental rabies in mice. Design: The effect of ribavirin on RABV multiplication was evaluated in vitro in both fibroblast (BSRT7) and neuroblastoma cell lines (SKN-SH) and also in vivo using an experimental rabies post-exposure treatment in C57BL6 mice, which were inoculated with different street RABV strains in different doses. Results: Ribavirin has a significant antiviral effect in both cell cultures. Orally-given ribavirin triggers a transient innate immune response in the mouse brain. Post-exposure oral treatment with ribavirin in mice provides no benefit against rabies Conclusion: Despite the significant effects of ribavirin on RABV multiplication in vitro, and the induction of an innate immune response in the brain, post-exposure oral treatment with ribavirin provides no benefit as a treatment for rabies.
Keywords: Rabies; Ribavirin; Innate immunity; Brain; Inflammation